2016
DOI: 10.1016/j.jbi.2016.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Drug repurposing for glioblastoma based on molecular subtypes

Abstract: A recent multi-platform analysis by The Cancer Genome Atlas identified four distinct molecular subtypes for glioblastoma (GBM) and demonstrated that the subtypes correlate with clinical phenotypes and treatment responses. In this study, we developed a computational drug repurposing approach to predict GBM drugs based on the molecular subtypes. Our approach leverages the genomic signature for each GBM subtype, and integrates the human cancer genomics with mouse phenotype data to identify the opportunity of reus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“… 5 The primary advantage of drug repositioning is that it starts from compounds with well-characterized pharmacology and safety profiles that can greatly reduce the risk of attrition in drug development in clinical phases. 6 We have recently developed novel computational algorithms that identified repurposed drug candidates to treat neuropsychiatric disorders, including schizophrenia 7 and Parkinson’s disease, 8 , 9 , 10 infectious diseases including dengue fever 11 and malaria; 12 cancers including glioblastoma; 13 , 14 and immune-mediated diseases including Crohn’s disease, 15 inflammatory bowel disease 16 and rheumatoid arthritis. 17 However, to date, systematic and comprehensive computation-based approaches to identify and validate drug-repositioning candidates for HGSOC have not been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“… 5 The primary advantage of drug repositioning is that it starts from compounds with well-characterized pharmacology and safety profiles that can greatly reduce the risk of attrition in drug development in clinical phases. 6 We have recently developed novel computational algorithms that identified repurposed drug candidates to treat neuropsychiatric disorders, including schizophrenia 7 and Parkinson’s disease, 8 , 9 , 10 infectious diseases including dengue fever 11 and malaria; 12 cancers including glioblastoma; 13 , 14 and immune-mediated diseases including Crohn’s disease, 15 inflammatory bowel disease 16 and rheumatoid arthritis. 17 However, to date, systematic and comprehensive computation-based approaches to identify and validate drug-repositioning candidates for HGSOC have not been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Mouse Genome Database (MGD) has made available large amounts of phenotypic descriptions of systematic gene knockouts in mouse models 35 . We have recently shown that these strong causal gene-phenotype annotations (278,553 gene-phenotype associations for 41,905 mutant alleles and 10,744 phenotypes) have great potential for virtual phenotypic screening for drug discovery 21 23 . In this study, we used gene-phenotype associations from MGD to assess the functional effects of top ranked microbial metabolites on CRC-related phenotypes.…”
Section: Methodsmentioning
confidence: 99%
“…The same modeling strategy used with bevacizumab can be applied to simulate the effect of other drugs. Recently, a drug repurposing in silico experiment which combines human genomic data with mouse phenotypes has suggested the possible utility of a number of drugs with different indications (see Table 3) for potential glioblastoma treatment (60). The intensity and the degree of heterogeneity in the response are very variable across the 8 drugs tested here.…”
Section: Effect Of a Drug At Single Cell Levelmentioning
confidence: 99%